2005
DOI: 10.1007/s11104-004-3551-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid whole-plant bioassay for phosphorus phytoavailability in soils

Abstract: Chemical P extraction from soils is an indirect and frequently questionable index for P availability. To monitor the dynamics of P availability in soils more directly following the application of P fertilizer, manure or sludge, a rapid, whole-plant bioassay was developed using tomato (Lycopersicon esculentum Mill.), Chinese cabbage (Brassica rapa L. var. pekinensis) and wheat (Triticum aestivum L.). Plant P extracted in 0.1 M H 2 SO 4 (P i ) and total P (P t ) concentration or content in stem, leaves or whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…After applying the different P sources, sludge materials or fertilizer-P, to the studied soil, P phytoavailability had changed with time. Based on the plant P i -content method (Huang et al, 2005), we found that KH 2 PO 4 applied at the rate of 150 mg P kg − 1 soil was rapidly fixed in less available forms in the soil: in terms of equivalent P fertilizer (compared to the same standard fertilizer at time zero), its P phytoavailability had decreased by 26% (to 110 mg P kg − 1 eqv.) during the first 14 days, and a further to 58% decrease (to 63 mg P kg − 1 eqv.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying the different P sources, sludge materials or fertilizer-P, to the studied soil, P phytoavailability had changed with time. Based on the plant P i -content method (Huang et al, 2005), we found that KH 2 PO 4 applied at the rate of 150 mg P kg − 1 soil was rapidly fixed in less available forms in the soil: in terms of equivalent P fertilizer (compared to the same standard fertilizer at time zero), its P phytoavailability had decreased by 26% (to 110 mg P kg − 1 eqv.) during the first 14 days, and a further to 58% decrease (to 63 mg P kg − 1 eqv.)…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, P phytoavailability in each tested soil is given in units of mg P fertilizer equivalent kg − 1 soil (equivalent P fertilizer, mg P kg − 1 eqv.). The P phytoavailability bioassay was described in detail by Huang et al (2005).…”
Section: P Phytoavailability Bioassaymentioning
confidence: 99%
“…Therefore, understanding the behavior of phosphate ester hydrolysis is important for biology and biogeochemistry as it is relevant to phosphate availability in the environment. 2,[38][39][40][41][42][43] Recently, we discovered that hydrolysis of G6P is significantly promoted by aged, acid-forced hydrolysed nanomolar iron solutions, and the presence of some tetrahedral oxyanions in solution act as inhibitors in an order of WO 4 . MoO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…These rhizosphere microorganisms obtain the carbon source and energy needed for survival from plant root exudates and litter 18 21 , but also provide many benefits for plants. For example, regulating the morphology and physiology of plants 22 , 23 , promote plant growth and damage repair 24 – 26 , increase plant tolerance to biological and abiotic stresses 27 – 29 , and improve plant ecological adaptability. Thus, the rhizosphere microbiome is considered as the second genome to plant condition 30 and serves on a highly evolved external functional environment for plants 31 , which are conducive to plant survival and population recovery.…”
Section: Introductionmentioning
confidence: 99%